Effect of collagen endometrial patch loaded with adipose-derived mesenchymal stem cells on endometrial regeneration in rats with a thin endometrium - Hong, Juyeon; Ahn, Hyojin; Moon, Soo Young; Kang, Hyo Jin; Yi, Kyong Wook (Frontiers in Endocrinology, 2023)
Background: This study aimed to investigate the effects of a collagen endometrial patch (EM patch) loaded with adipose-derived mesenchymal stem cells (ADSCs) on endometrial regeneration in a rat model with thin endometrium.Thin endometrium was induced in female rats and divided into treatment groups as outlined: control, group 1(G1), local injection of ADSCs into the uterus, group 2 (G2), an EM patch without ADSCs, group 3 (G3), and an EM patch loaded with ADSCs, group 4 (G4). The rats were euthanized at either two weeks or four weeks after modeling and treatment followed by histological and biochemical analyses to examine the regenerative effects on the injured endometrium.Results: Transplantation of the ADSC-loaded EM patch significantly promoted endometrial proliferation and increased the luminal epithelial area. Two weeks after treatment, the mean number of von Villebrand factor (vWF) + or cluster of differentiation (CD) 31 + -stained blood vessels was significantly higher in G4 than in G1 and G2. The mRNA and protein expression levels of TGF-β and FGF2 were significantly upregulated in G4 compared to those in the control. G4 exhibited significantly increased LIF mRNA levels and immunoreactivity compared with the other groups at both two weeks and four weeks after treatment. Cell tracking after ADSCs treatment revealed the presence of a substantial number of ADSCs grafted in the uterine tissues of G4, whereas a low number of ADSCs that were focally clustered were present in G2.Transplantation of EM patches loaded with ADSCs resulted in the histological and biochemical restoration of an injured endometrium. The strategic integration of EM patches and ADSCs holds significant promise as an innovative therapeutic approach for effectively treating impaired endometrial conditions.